1985
DOI: 10.1007/bf02560223
|View full text |Cite
|
Sign up to set email alerts
|

Enteroclysis in the diagnosis of chronic unexplained gastrointestinal bleeding

Abstract: In a six-year period (1977-83), lesions were identified by enteroclysis in 26 patients with melena or recurrent gastrointestinal bleeding undiagnosed by other modalities. These included nine Meckel's diverticula, three metastatic lesions, three primary carcinomas, one lipoma, four leiomyomas, five surgically created blind pouches, one carcinoid, and one idiopathic dilatation of the ileum. Our experience suggests that, when the standard diagnostic procedures used to investigate chronic gastrointestinal blood lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…These lesions, as well as some other structural lesions of the small intestine including mass lesions, ulcers, and Crohn's disease, may be detected by barium contrast studies of the small intestine. The literature suggests that small bowel enema techniques (enteroclysis) may have an increased diagnostic yield over standard small bowel follow-through series (45,46).…”
Section: Ajg -August 1998mentioning
confidence: 99%
“…These lesions, as well as some other structural lesions of the small intestine including mass lesions, ulcers, and Crohn's disease, may be detected by barium contrast studies of the small intestine. The literature suggests that small bowel enema techniques (enteroclysis) may have an increased diagnostic yield over standard small bowel follow-through series (45,46).…”
Section: Ajg -August 1998mentioning
confidence: 99%
“…Several studies in the literature have reported a greater diagnostic yield for enteroclysis than for small bowel follow-through. (7)(8)(9)(10)(11)(12). For gastrointestinal bleeding the diagnostic yields range from 10 to 25% (13)(14)(15).…”
mentioning
confidence: 99%
“…SBE studies have been advocated for the detection of a variety of small-bowel diseases, including small-bowel obstruction, gastrointestinal bleeding, and Crohn's disease [5][6][7][8][9]. In a recent study by Maglinte et al [10], SBE studies were found to be accurate in excluding Crohn's disease when a carefully performed SBE was normal.…”
Section: Discussionmentioning
confidence: 98%